The Development of the Agricultural Sector of Colombia into the 1960s - Berry, Albert (Editorial Universidad del Rosario, 2017)
For various reasons it was not revised and edited for publication at that time. In view of the important events currently transpiring in and around the agricultural sector of Colombia and the possible usefulness of additional historical material, it is now being published essentially as it was left in the late 1960s. I have not reviewed the available material in detail recently, so their may be errors of fact that I am not aware of, either in the numbers presented or of other sorts. Many useful studies of Colombian agriculture have been undertaken in the interim, though they may not have covered the same material as included here. Because of the unrevised nature of the material the mode of presentation varies from chapter to chapter. Table numbers are not continuous (i.e. there may be no Table 5 in a given chapter) but their order has been maintained, sometimes through the use of decimals (e.g. Table 10.1).